2013
DOI: 10.1016/j.nedt.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Student nurses' perspectives of spirituality and spiritual care

Abstract: Participating student nurses reported a high level of spiritual awareness that was not constrained by age. Students affirmed the importance of spiritual awareness in order to address the spiritual needs of patients. There was some congruence between the perceptions of students in this ethno-culturally diverse Asian sample and responses by students in the UK and North America on the personal attributes needed to provide spiritual care. Comparative studies using the SCGS could inform our understanding of spiritu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 36 publications
1
36
2
2
Order By: Relevance
“…This in contrast with the findings of Tiew et al (2013a) that student nurses perceived spiritual care as an integral component of human beings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This in contrast with the findings of Tiew et al (2013a) that student nurses perceived spiritual care as an integral component of human beings.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were found in previous studies which suggest that females, rather than males, tend to study within the health field such as social work and nursing which indicated greater numbers of women students (Bhagwana 2010;Tiew et al 2013a;Wong et al 2008;Tiew et al 2013b;Ross et al 2013). …”
Section: Discussionsupporting
confidence: 89%
“…The literature suggests that, spiritual awareness is necessary for spiritual assessment (Pesut, 2002, Baldacchino, 2008a, Tiew et al, 2013, and specific education on spirituality provide a broader view of diverse beliefs Drury, 2012, Wallace et al, 2008) and enabled students to grow in terms of sensitivity to their personal spiritual agendas (Baldacchino, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was a small study and Tiew et al (2013) went on to conduct a survey of 745 student nurses in Singapore to investigate perceptions of spirituality and spiritual care, using a spiritual care-giving scale (SCGS) (Tiew and Creedy, 2012).…”
Section: Spiritual Awarenessmentioning
confidence: 99%
See 1 more Smart Citation